Comparing the use of physical manipulatives and virtual manipulatives in seesaw in improving low-performing incoming first-grade pupils’ achievement in addition - Santiago, Marian Jo Veronica H. (Animo Repository, 2023)
This study compares the use of physical manipulatives and virtual manipulatives in Seesaw in improving low-performing incoming first-grade pupils’ achievement in Addition within 20. It explores how pupils perform before and after using the manipulatives, how they demonstrate adaptive mathematical reasoning while using the manipulatives, what their experiences and attitudes are when using the manipulatives, and how using manipulatives can be improved to better teach low-performing pupils. The study employed a single-subject design to explore each pupils’ experiences with the manipulatives. Five pupils were randomly assigned to one of two groups. One group received instruction with virtual manipulatives while the other received instruction with physical manipulatives. A pretest was administered before the activities and a posttest and survey were administered after. It was found that both the physical and virtual manipulatives did not significantly improve their performance in Addition within 20. It was, however, found that the manipulatives helped pupils transition from concrete experiences to the abstract level of addition, communicate the process of addition, reflect on their work, and correct errors. The pupils had positive experiences with both activities, citing that they enjoyed practicing mathematics skills with the manipulatives, using the different Seesaw features, and using various physical manipulatives.